Socio-Economic and Psychological Effects of Dengue upon the Patients in Faisalabad - Zia Mahmood, Munazzah Manzoor, Shabbir Ahmad, Saira Akhtar, Usman Habib, Zaighum Aqeel Atif (Pakistan Journal of Medical & Health Sciences, 2022)
The rise in the incidence of dengue in Pakistan has adversely affected the country’s developing economy and also its health planning. Dengue is an illness with profound social, economic, and health effects and costs to the Pakistani society. In many developing countries dengue outbreaks are a source of huge economic burden. Dengue has important economic consequences because of the burden to hospitals, work absenteeism and risk of death of symptomatic cases. The causal relationship between a physical illness and the psychological symptoms is a well-known phenomenon. A cross-sectional research was carried out in Faisalabad involving patients who were diagnosed to have dengue fever. Face to face interviews using interview schedule were carried out. 150 respondents were selected using simple random sampling from the sampling frame of the patients’ list. 36.7 % of the respondents were of the view that low income to adopt preventive measure was the major cause of dengue. 51.3 % of the patients felt psychological issues like depression, anxiety and post traumatic disorder. In bivariate analysis, a non-significant relationship was found between income and tendency of preventive measure which reflected that people from all income groups were prone to be affected. However, significant relationship between education and preventive measure was observed. The government should make a holistic approach to consider the social, economic and psychological effects of dengue upon the patients.